Charged Hadron Multiplicity Distribution at Relativistic Heavy-Ion Colliders - Ashwini Kumar; P. K. Srivastava; B. K. Singh; C. P. Singh (Advances in High Energy Physics)
The present paper reviews facts and problems concerning charge hadron production in high energy collisions. Main emphasis is laid on the qualitative and quantitative description of general characteristics and properties observed for charged hadrons produced in such high energy collisions. Various features of available experimental data, for example, the variations of charged hadron multiplicity and pseudorapidity density with the mass number of colliding nuclei, center-of-mass energies, and the collision centrality obtained from heavy-ion collider experiments, are interpreted in the context of various theoretical concepts and their implications. Finally, several important scaling features observed in the measurements mainly at RHIC and LHC experiments are highlighted in the view of these models to draw some insight regarding the particle production mechanism in heavy-ion collisions.